2014
DOI: 10.1155/2014/151723
|View full text |Cite
|
Sign up to set email alerts
|

GCKGene-Body Hypomethylation Is Associated with the Risk of Coronary Heart Disease

Abstract: Objectives. Glucokinase encoded by GCK is a key enzyme that facilitates phosphorylation of glucose to glucose-6-phosphate. Variants of GCK gene were shown to be associated with type 2 diabetes (T2D) and coronary heart disease (CHD). The goal of this study was to investigate the contribution of GCK gene-body methylation to the risk of CHD. Design and Methods. 36 patients (18 males and 18 females) and 36 age- and sex-matched controls were collected for the current methylation research. DNA methylation level of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 45 publications
(59 reference statements)
1
33
1
1
Order By: Relevance
“…This observation indicated that EH was affected by genetic and environmental factors, including DNA methylation status and age. Age was previously revealed to be positively correlated with GCK methylation levels (23), however the present study failed to demonstrate this association. No association between age and CpG1-3 or CpG4 methylation was observed (data not shown).…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…This observation indicated that EH was affected by genetic and environmental factors, including DNA methylation status and age. Age was previously revealed to be positively correlated with GCK methylation levels (23), however the present study failed to demonstrate this association. No association between age and CpG1-3 or CpG4 methylation was observed (data not shown).…”
Section: Discussioncontrasting
confidence: 96%
“…Hypermethylation of gene-bodies frequently indicates higher levels of gene expression in human tissues and cell types (8,31). Aberrant methylation of the gene body was observed to contribute to the risk of heart failure (32) and coronary heart disease (23). DNA methylation of gene bodies has major significance in the regulation of gene expression (33).…”
Section: Discussionmentioning
confidence: 99%
“…Genomic DNA was isolated from tumor samples and then quantified as previously described (11,17). TGFB2 and BCL2L11 methylation levels were measured using bisulfite pyrosequencing technology.…”
Section: Tissuementioning
confidence: 99%
“…DNA conversion was performed using reagents provided in the Zymo EZ DNA Methylation-Gold kit (Zymo Research, Orange, CA, USA). The pyrosequencing procedures were performed as described previously (11,17). The primer sequences of TGFB2 were 5'-GAGTAATTTTAAGTTGGGGAGAAGTTAGT-3' for the forward primer, 5'-Biotin-ACT CCA AAC CCC AAC CCA ACCA-3' for the reverse primer, and 5'-CCA ACC CAA CCA CAA-3' for the sequencing primer.…”
Section: Tissuementioning
confidence: 99%
See 1 more Smart Citation